Análise in silico e de expressão da família gênica Ethylene Response Factors (ERF) no gênero Malus. - Cero, Joceani Dal (2010)
Regulatory molecules, such as transcription factors, have been thoroughly investigated, especially in hormone-mediated responses that involve gene expression modulation. Frequently, the main determinant of gene expression is its transcriptional rate. Thus, molecular mechanisms underlying transcription regulation have become an important topic in genetic studies of ethylene signaling. The present work aimed to investigate the ERF (Ethylene Response Factor) family employing bioinformatic tools, integrating publicly available datasets from the model species Arabidopsis thaliana and phylogenetic analyses to help elucidating the biological roles of the family in apple. The preliminary survey of the ERF sequences in Malus has provided basic information to be incorporated in further studies of the functional role of ERFs in this perennial species. Expression analyses of MdERF1 and MdERF in apple fruits suggest that other factors, besides ethylene, are involved in their transcriptional regulation in Malus. The second chapter reports the investigation of the transcriptional profiling of those ERF genes in response to pathogen attack, using a biological assay of in vitro propagated plants inoculated with the fungus Venturia inaequalis (apple scab disease). The study has provided evidences of the involvement of MdERF1 in eliciting the plant response; whereas, MdERF2 does not appear to be participate in the pathogenesis.